Evaluation of semi-automated cells counting in peritoneal fluid - Daikelly I. Braghirolli; Patricia Pranke; Luciane N. Calil (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTIntroduction:Currently, the cytological analysis of biological fluids, such as peritoneal fluid, is performed by manually cells counting in Fuchs-Rosenthal chamber. However, this method has a number of limitations. Because of these limitations, automatic counters have been evaluated for cell counting in this type of sample in order to make it faster and more reliable test.Objective:The aim of this study is to compare the manual and semi-automated leukocytes and erythrocytes counting in peritoneal fluid.Materials and methods:The samples were analyzed manually and using the CountessTM(Invitrogen).Results:The results showed that although there is a correlation between the two counting methods, the correlation is relatively low, for both leukocytes and erythrocytes analysis.Conclusion:The results suggest that peritoneal fluid should continue to be analyzed in Fuchs-Rosenthal chamber. However, further studies should be conducted with a greater number of samples to investigate the possibility of using automated cells counting in serous fluids and, thus, provide greater speed and quality of results.